Assessment of knowledge, attitudes, and practices regarding TB prevention and treatment among college students in Wuhan, central China - Wu, Gang; Quan, Chao; Yu, Aiping; Li, Li; Chen, Jun; Yang, Yun; Wang, Guiyang; Lu, Zhouqin; Wang, Xiaojun; Duan, Qionghong; Zhang, Haoze; Hu, Jing; et al. (Frontiers in Tuberculosis, 2025)
BackgroundTuberculosis (TB) is recognized as a serious public health concern in many developing countries. As the new main force and inheritors of national health construction, college students bear important social responsibilities and missions of practicing TB prevention and control, volunteer mobilization, and health concept dissemination. Improving college students' health literacy is crucial to preventing and treating infectious diseases. This study aims to assess college students' knowledge, attitudes, and practices (KAP) about TB prevention and treatment in Wuhan, China.MethodsA descriptive cross-sectional study survey among college students was conducted from May to June 2022 at 22 colleges using the judgment sampling method in Wuhan. KAP regarding TB was recorded and assessed using an online questionnaire platform. The status quo of KAP regarding TB prevention and treatment was statistically described, and the formation of students' TB prevention and treatment behavior was analyzed using single-factor and multifactor logistic regression.ResultsA total of 15,290 college students completed the questionnaire, and 15,272 valid questionnaires were collected. The total awareness rate of knowledge, attitudes, and practices of TB prevention and treatment was 79.69%. Among them, the awareness rate of key knowledge was 79.28%, and the passing rate was 92.46%. The holding rate of correct attitudes was 89.69%, and the passing rate was 90.56%. The formation rate of correct behaviors was 72.11%, and the passing rate was 96.62%. A single-factor analysis showed that gender, grade, parents' education level, contact history of TB patients, and passing rate of key knowledge were statistically different in the formation of prevention and treatment behaviors. Multivariate logistic regression analysis showed that for females (odds ratio [OR] = 1.86, 95% CI [1.50, 2.30], p < 0.01), students with father's educational background of primary school (OR = 2.94, 95%CI [1.62, 5.33], p < 0.01), junior school and equivalent (OR = 2.94, 95%CI [1.62, 5.33], p < 0.01), high school and equivalent (OR = 3.05, 95%CI [1.70, 5.46], p < 0.01), and diploma or undergraduate (OR = 3.24, 95% CI [1.73, 6.09], p < 0.01); no history of TB (OR = 3.32, 95% CI [1.49, 7.41], p < 0.01); a passing key knowledge score (OR = 9.91, 95% CI [8.11, 12.11], p < 0.01); and a passing attitude score (OR = 7.35, 95% CI [6.01, 8.99], p < 0.01) were likely to form TB prevention and treatment behaviors.ConclusionSchool health promotion should not only focus on improving students' personal knowledge and skills of TB prevention and treatment but also emphasize the level of family participation, strengthen the comprehensive mobilization action of schools, formulate policies to support health action, create a supportive social environment, and radiate the health education effect of students to the whole society.